Cardiac myxoma with glandular elements: A case report - K.C., Bibek; Karki, Shovana (Journal of Pathology of Nepal, 2017)
Cardiac myxoma with glandular elements is extremely rare cardiac myxomas that show glandular differentiation, the pathogenesis of which is unknown. The present case study reports a case of glandular cardiac myxoma. A 21-years-old female presented with left atrial mass which was surgically resected and sent for histopathological examination. Microscopically, there were well formed mucinous glands in a background of cardiac myxoma and hence cardiac myxoma with glandular elements was confirmed. Though rare, it should always be differentiated from metastatic adenocarcinoma.